Evaluation of Green Infrastructure Benefits in Urban Areas in Paris - Lemoine, Elise (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to investigate the evaluation of green infrastructure benefits in urban areas in Paris. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: An evaluation of green infrastructure benefits in urban Paris found that parks and street trees effectively mitigate urban heat island effects and improve air quality by reducing pollutants such as nitrogen dioxide and particulate matter. Recommendations emphasize integrating green infrastructure into urban planning to sustain these benefits and promote environmental resilience, highlighting its critical role in enhancing urban livability and sustainability in Paris. Unique Contribution to Theory, Practice and Policy: Ecosystem services framework, social-ecological Systems (SES) theory & urban political ecology (UPE may be used to anchor future studies on the evaluation of green infrastructure benefits in urban areas in Paris. Foster interdisciplinary collaboration between urban planners, landscape architects, environmental scientists, and social researchers to enhance the design, implementation, and management of green infrastructure projects. Advocate for policy frameworks that integrate green infrastructure into urban planning and development strategies at local, regional, and national levels. This includes incentivizing green infrastructure adoption through financial incentives, tax breaks, and regulatory support.